2016
DOI: 10.15406/ghoa.2016.05.00136
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Cells: Key Players in Hepatocellular Carcinoma Progression

Abstract: Hepatocellular carcinoma (HCC) represents a major health problem and ranked as the sixth most common cancer worldwide and the third most common cause of cancerrelated mortality. The prognosis of HCC is usually poor due to post surgery recurrence and metastasis. Both Cells mediated and humoral immunity is considered as key players in the immunopathology of HCC. Recently, there is a special subset of B cells defined as regulatory B cells (Bregs) found to be abundant in the tumor microenvironment and was a leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…BCR signaling activates multiple signaling cascades involving kinases, GTPases and transcription factors, and contributes to survival and proliferation. While activation of B cells in the tumor microenvironment is known to promote the progression of various cancers, including HCC (Hetta et al, 2016), it is possible that the continuously activated immune pathways contributed to the survival of tumor hepatocytes during tumor regression. Ingenuity canonical pathway analysis revealed that the Gα12/13 and NGF signaling, which were upregulated in tumor hepatocytes, retained their activation state in tumor-reverted hepatocytes but not in the newly differentiated hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…BCR signaling activates multiple signaling cascades involving kinases, GTPases and transcription factors, and contributes to survival and proliferation. While activation of B cells in the tumor microenvironment is known to promote the progression of various cancers, including HCC (Hetta et al, 2016), it is possible that the continuously activated immune pathways contributed to the survival of tumor hepatocytes during tumor regression. Ingenuity canonical pathway analysis revealed that the Gα12/13 and NGF signaling, which were upregulated in tumor hepatocytes, retained their activation state in tumor-reverted hepatocytes but not in the newly differentiated hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is considered one of the most common malignancies and major health problems worldwide . In Egypt, HCC is the second most common cancer in men and the sixth most common cancer in women . Hospital‐based studies from Egypt have reported an overall increase in the relative frequencies of all liver‐related cancers in Egypt, from approximately 4% in 1993 to 7.3% in 2003 …”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in curative treatment modalities for HCC including surgical resection, liver transplantation and radiofrequency ablation [5][6][7][8], high recurrence rates still limit overall patients' survival [9]. Therefore, understanding the fundamental biological changes in HCC responsible for its rapid growth and metastasis is essential to guide the development of new therapeutic options [10][11][12].…”
Section: Introductionmentioning
confidence: 99%